2010
DOI: 10.1089/fpd.2009.0358
|View full text |Cite
|
Sign up to set email alerts
|

Salmonellaspp. Infection in Imported 1-Day-Old Chicks, Ducklings, and Turkey Poults: A Public Health Risk

Abstract: The occurrence of Salmonella in 750 birds was assessed. The samples included the internal organs (caecal pouches, yolk sac, liver, and lung) of imported 1-day-old chicks (n = 150), grandparent chicks (n = 150), breeder chicks (n = 150), ducklings (n = 150), and turkey poults (n = 150), and paper-lined boxes (n = 250). Salmonellae isolated from the internal organs and paper-lined box of 1-day-old chicks, ducklings, and poults were mostly evident from the paper-lined box followed by caecal samples. Imported 1-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 22 publications
3
15
1
Order By: Relevance
“…Salmonella-specific PCR with primers for the invA gene is a rapid, sensitive, and specific means for monitoring Salmonella at the genus level in a variety of clinical samples [34]. The present study supported the ability of these specific primer sets to confirm the isolates as Salmonella.…”
Section: Discussionsupporting
confidence: 77%
“…Salmonella-specific PCR with primers for the invA gene is a rapid, sensitive, and specific means for monitoring Salmonella at the genus level in a variety of clinical samples [34]. The present study supported the ability of these specific primer sets to confirm the isolates as Salmonella.…”
Section: Discussionsupporting
confidence: 77%
“…but not all serovars that occur in breeding flocks can be found in the hatchery and contaminated feed is also an important source . The vertically transmitted turkey S. Arizonae strains (Crespo et al, 2004) were not found in the survey but many serovars were the same as those previously related to world trade in turkey breeders (Beli et al, 2001;El-Agroudi, 1964;Hadad, 1996;Hird et al, 1993;Irwin et al, 1994;Koncicki et al, 2000;Osman et al, 2010;Papadopoulou et al, 2009;Pedersen et al, 2002) although detailed molecular epidemiology would be needed to confirm transmission routes as well as sources of human cases (Anderson et al, 2010). Some serovars such as S. Senftenberg readily colonise feed mills and hatcheries and can be found at a low prevalence in turkeys (Edwards, 1937;Lecuyer et al, 1996;Pedersen et al, 2008).…”
Section: Impact Of Salmonella Prevalence In Flocks Of Breeding Turkeysupporting
confidence: 59%
“…14,21,[33][34][35] The high frequency of Salmonella recovery from imported DOD causes great public health concern due to the zoonotic potential of this pathogen and its economical importance to commercial poultry breeding. successfully confirmed the importance of hatchery contamination and Salmonella dissemination.…”
Section: Discussionmentioning
confidence: 99%
“…The 14 Salmonella serovars isolated from the imported DOD were substantially different from previous scientific literature. [1][2][3][5][6][7]11,13,14,34,45 The isolated serovars of DOD in the current investigation have not been previously reported in Egypt; 21 moreover, because contracting Salmonella causes adverse health effects and even mortality in humans, 46 this study may provide additional evidence that may be used to address this impending global public health issue in the future. 47,48 The high prevalence (5/34) of detected S. enteritidis is evident by the fact that serovar S. enteritidis may have contributed to filling the gap of an ecologic niche, apparent by the considerable increase in S. enteritidis prevalence after the eradication of biovar Gallinarum in the 1960s.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation